Front-end de RF baseado em tecnologias fot?nicas para as redes 5G - Muniz, Andr? Luiz Marques (2017)
This work is regarding the development of a photonics-based RF front-end and its experimental performance analysis. The proposed device presents ultra-wideband operation from a few kHz to 40 GHz, by means of simultaneously applying two techniques: RF signal generation, using frequency multiplication, and RF amplification, both in the optical domain. The RF front-end implementation in a real optical-wireless network demonstrates its applicability in three potential frequency bands of 5G cellular networks, namely: 6, 28 and 38 GHz. The experimental performance investigation was based on RF and optical parameters, including optical power, signal-to-noise ratio (SNR), RF gain, phase noise and error vector magnitude (EVM). RF gain of 27 dB over the entire band has been obtained, as well as improvement of 13.4 dB and 15 %RMS in the SNR and EVM, respectively, when compared to a conventional radio over fiber system. The main dissertation contributions are the concept, development and validation of a photonics-based RF front-end, which provides frequency tunability, high gain and signal distortion absence.